Welding and metal fabrication - Jeffus, Larry F. (Delmar, 2012)
A welding and metalwork textbook combines the skills of measuring, cutting, shaping, fitting, welding, and finishing and includes hands-on exercises, experiments, and projects.
Includes index.
Keywords: Welding.; Metal-work.; elektronické knihy; electronic books